Integrative transcriptomics and phenotyping uncover genetic networks controlling fruit quality in two strawberries (Fragaria × ananassa) - Chen, Yubo; Liu, Hainan; Jiang, Ting; Song, Kangjian; Zhang, Xueming; Zhang, Maojun; Yao, Huanyu; Duan, Xiande; Duan, Mingzheng; Rao, Muhammad Junaid (Frontiers in Plant Science, 2026)
Strawberry fruit quality is a complex trait governed by molecular mechanisms that undergo dynamic changes during ripening. This study investigated two varieties with contrasting phenotypes: ‘Monterey’, a firm-fleshed commercial cultivar, and ‘Three Princess’, a softer, sweeter variety. We analyzed five key developmental stages (green, white, transfer color, red, and overripe) to unravel the transcriptional basis of their divergent quality traits. RNA-seq revealed extensive differential gene expression (11,382 DEGs at the red stage, FDR < 0.05), with ‘Three Princess’ showing earlier activation of starch/sucrose metabolism and specific polygalacturonases (Fxa1Ag102477), correlating with its rapid softening and higher soluble solids content (SSC). WGCNA identified co-expression modules strongly linked to hardness, including MElightsteelblue1 (positively correlated) and MEantiquewhite1 (negatively correlated). Crucially, we found that firmness retention in ‘Monterey’ was associated not with the suppression of polygalacturonases but with the sustained high expression of key NAC transcription factors like Fxa2Dg203497, suggesting a potential transcriptional mechanism associated with delayed softening. Enriched pathways like galactose metabolism and fatty acid degradation further highlighted metabolic shifts driving texture and sweetness. Our findings demonstrate that varietal differences in fruit quality are determined by a stage-specific transcriptional interplay between cell wall-disassembling enzymes and their transcriptional regulators. These results provide candidate genes and regulatory networks for breeding strawberries with optimized texture and flavor, advancing our understanding of the complex molecular mechanisms governing strawberry fruit quality during ripening.